Verifying Policy-Based Security for Web Services - Bhargavan, Karthik; Fournet, Cédric; Gordon, Andy (2004)
WS-SecurityPolicy is a declarative language for configuring web services security mechanisms. We describe a formal semantics for WS-SecurityPolicy and propose a more abstract language for specifying secure links between web services and their clients. We present the architecture and implementation of tools that (1) compile policy files from link specifications, and (2) verify by invoking a theorem prover whether a set of policy files run by any number of senders and receivers correctly implements the goals of a link specification, in spite of active attackers. Policy-driven web services implementations are prone to the usual subtle vulnerabilities associated with cryptographic protocols; our tools help prevent such vulnerabilities. We can verify policies when first compiled from link specifications, and also re-verify policies against their original goals after any modifications during deployment. Moreover, we present general security theorems for all configurations that rely on compiled policies.
CCS '04 Proceedings of the 11th ACM conference on Computer and communications security